In vitro effect of green tea and turmeric extracts on GLP-1 and CCK secretion: the effect of gastrointestinal digestion. Issue 10 (18th September 2018) - Planes-Muñoz, David; López-Nicolás, Rubén; González-Bermúdez, Carlos A.; Ros-Berruezo, Gaspar; Frontela-Saseta, Carmen
Abstract : Plant extract activity can be modified by the digestion process. Abstract : Plant extract activity can be modified by the digestion process. In order to assess the satiety effect of green tea and turmeric extracts, an in vitro gastrointestinal digestion process was performed and the STC-1 cell line was used. The enteroendocrine cell line was incubated (for 30, 60 and 120 minutes) with the digested and non-digested extracts measuring the secretion of cholecystokinin (CCK) and glucagon-like peptide-1 (GLP-1) by enzyme-linked immunosorbent assay (ELISA). The release of satiety hormones by the STC-1 cells showed similar or higher results for plant extracts compared to the positive controls reported as satiatogenic (proteins and short chain fatty acids). For the non-digested samples, the largest amount of CCK and GLP-1 was found for turmeric, with 379 ± 46 pg ml −1 (60 min) and 347 ± 125 pg ml −1 (120 min) respectively. For the digested samples, the highest level of CCK was found for turmeric at 30 minutes (43.3 ± 11) and for GLP-1 by green tea at 120 minutes (165.7 ± 52). The in vitro gastrointestinal digestion process affects the satiety of plant extracts, increasing for green tea and decreasing for turmeric. Green tea showed the most stable satiating capacity after the in vitro digestion process and this may be useful for using it as a stable food supplement to reduce hunger associated with overweight and obesity.